Community leaders' perceptions toward tourism impacts and level of building community capacity in tourism development - Aref, Fariborz; Redzuan, Ma'rof (Canadian Center of Science and Education, 2009)
This paper investigates relationship between the community leaders’ perceptions toward tourism impacts and their support in building capacity for tourism development in local communities of Shiraz, Iran. Pearson correlation was used to examine relation between tourism impacts and level of community capacity building in tourism development. According to the survey, the strongest relationship between perceptions toward tourism impacts and level of community capacity building are found to be linked with its economic impacts of tourism, while environmental impacts are found to be significant negatively with level of community capacity building.